Strategi Pemasaran Digital dalam Meningkatkan Branding pada Bisnis Busana Muslim di Toko “Hilya Collection” Lamongan - Anna Putri Syafitri (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
This study aims to analyze the digital marketing strategies implemented to enhance branding in the Muslim fashion business at the "Hilya Collection" Store in Lamongan. Using a deductive qualitative approach, data were obtained through online interviews and literature studies from various sources, such as books, articles, journals, and relevant social media. The "Hilya Collection" Store utilizes social media for product promotion, collaborating with agents and resellers through WhatsApp groups, Instagram Reels, Shopee accounts, Facebook, and TikTok. This digital marketing strategy helps the store build strong branding, increase customer trust, and expand its market reach globally. With consistent implementation of the right digital strategy, this business can compete in a wider market, reach more Muslim customers, and have a positive impact on the store's development. It is hoped that the implementation of this digital marketing strategy will continue to support the growth and success of the "Hilya Collection" Store in facing increasingly fierce market competition.